Forming Ethical Resilience in Students in the Digital Age: Historical Experience and Leadership Practice - Rasulov Baxtiyor Maxmudjonovich (Global Academy of Multidisciplinary Studies, 2026)
Purpose: This study explores the formation of ethical resilience among students in the context of digital transformation. It integrates historical pedagogical values with modern leadership practices to identify strategies for protecting students from "information attacks" and ethical erosion. Research Methodology: A mixed-methods approach was used, combining historical analysis with a survey of 120 students and 15 department heads at Andijon State Pedagogical Institute (ADPI). Data were analyzed using SPSS, focusing on perceptions of ethical resilience and leadership impact. Results: The study found that students exposed to historical pedagogical modules showed greater ethical resilience, with higher moral discernment in evaluating information sources. Leadership practices emphasizing "Visible Integrity" and "Ethical Transparency" were particularly effective in improving students’ media immunity. Conclusions: The research highlights that ethical resilience is a dynamic process, shaped by both national heritage and transformational leadership. The findings suggest that digital leadership must evolve to include "Ethical Mentorship" alongside digital literacy. Limitations: The study is limited to ADPI and may not be generalizable across other institutions. Future research should expand to different educational contexts. Contributions: This research contributes to the understanding of how historical and modern educational practices can integrate to enhance ethical resilience, offering a framework for higher education to foster ethical and digital literacy.